Analysis of Profitability Ratios on Stock Returns in Healthcare Service Providers on IDX (2020–2024) - Septyadi, Rendy; Sari, Diana (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the influence of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Earnings per Share (EPS) on stock returns in healthcare service provider companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative approach with multiple linear regression methods was employed. The sample consists of seven healthcare companies selected using purposive sampling criteria, including consistent publication of audited annual financial reports and accessible stock return data. Classical assumption tests were conducted to ensure model validity, followed by t-tests, F-tests, and the coefficient of determination (R²) to examine the partial and simultaneous effects of the independent variables on stock returns. The results show that Return on Assets (ROA) and Earnings per Share (EPS) have a positive and significant impact on stock returns, indicating that asset utilization efficiency and earnings potential per share are key considerations for investors. In contrast, Return on Equity (ROE) and Net Profit Margin (NPM) do not exhibit significant effects, suggesting that capital effectiveness and operational efficiency have not been fully appreciated by the market in this sector. These findings suggest that the Indonesian stock market is not yet fully efficient in the semi-strong form and provide theoretical support for the application of signaling theory and market efficiency theory in the healthcare sector.